Stability analysis of the false roof made of cemented tailings backfill in deep mine: A case study - Gang Xu; Xingping Lai; Pengfei Shan; Jianning Liu; Huicong Xu; Hao Wang (Case Studies in Construction Materials)
The overall stability of cemented tailings backfill (CTB) false roof, as an important support structure in the quarry, is of great significance for realizing the safe recovery of the ore body. This paper aims at the practical problem of ore body mining under the condition of deep broken rock mass. By analyzing the typical process characteristics of underhand cut-and-fill mining method, the dangerous mechanical state of CTB false roof is determined, and the CTB false roof strength model based on the maximum tensile stress failure criterion and deep mining coefficient is established. Based on the measured load value of CTB false roof, the minimum required strength of CTB false roof is obtained. Through the performance tests of CTB under different proportioning schemes, the mechanical strength of CTB false roof (UTS：0.43 MPa, UCS：6.22 MPa) is designed，the proportioning parameters of CTB with ''high strength, high fluidity, quick setting and low cost'' are put forward. Finally, based on FLAC3D numerical simulation and field monitoring, the stability of CTB false roof with recommended ratio parameters is analyzed. The results show that the CTB false roof has not been violently displaced and destabilized in the process of service ore body mining, has good strength reserve, and is able to provide a safe workspace for mining, verifies the reliability and reasonableness of the CTB false roof proportioning parameter, and provides a new way for the study of false roof stability.